2006
DOI: 10.1094/pd-90-0378b
|View full text |Cite
|
Sign up to set email alerts
|

A New Begomovirus Inducing Yellow Mottle in Okra Crops in Mexico is Related to Sida yellow vein virus

Abstract: Okra (Abelmoschus esculentus L. Moench), an annual vegetable of African origin, has been cultivated in Mexico for 3 decades. Since 2000, the most important okra-producing areas in the states of Guerrero and Morelos have been affected by a disease causing yellow streak and severe distortion of fruits, a bright yellow mottle, and curling and distortion of leaves. These symptoms and the presence of whiteflies (Bemisia tabaci Gennadius) suggest a viral etiology. Samples of symptomatic plants from three localities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The malvaceous plants in the New World are affected by bipartite begomoviruses [ 27 - 29 ] betasatellites not apparently occurring in the New World [ 7 ]. In the Old World begomoviruses infecting okra are invariably associated with betasatellites and are, for the few which have been characterized, monopartite--lacking the DNA B component.…”
Section: Discussionmentioning
confidence: 99%
“…The malvaceous plants in the New World are affected by bipartite begomoviruses [ 27 - 29 ] betasatellites not apparently occurring in the New World [ 7 ]. In the Old World begomoviruses infecting okra are invariably associated with betasatellites and are, for the few which have been characterized, monopartite--lacking the DNA B component.…”
Section: Discussionmentioning
confidence: 99%
“…A new begomovirus species, okra yellow crinkle virus (OYCrV) (Shih et al, 2006), was recently shown to be associated with OLCD in Mali. In other parts of the world, similar diseases of okra are also associated with begomovirus infection (De La Torre-Almaraz et al, 2006;Idris & Brown, 2002;Jose & Usha, 2003;Zhou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…. Viral DNA amplifications were carried out using the universal primers for begomoviruses: pRep-DGR (Méndez et al, 2006), PrCP70-Mot, prRepQGR-rev (De la Torre et al, 2006) and prC889 (Brown et al, 2001). The PCR products comprise the complete A component.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%